Prognosis of patients with tracheal intubation in the emergency department. (December 2021) - Sarbazi-Golezari, Ali; Namdar, Peyman; Yousefian, Shiva; Mirzadeh, Monirsadat; Farnood, Afsaneh; Modirian, Ehsan
Abstract: Background: Intubation of critically ill patients is one of the increasing emergency procedures. We designed this study to determine age and sex-related mortality rates after emergency intubation. Methods: This retrospective study collected and analyzed non-trauma intubated patients in a referral hospital from the years 2017–2019 and before the appearance of COVID-19. Patients who were intubated outside of emergency by EMS technicians were excluded. We recorded data of intubated patients, like sex, age, length of being intubated and final diagnosis. P values of less than 0.05 were significant. Results: Data of 520 non-trauma intubated patients were collected and analyzed. More than 64% of the patients were over 65 years old and had a higher mortality rate (86.7%; P < 0.001) than younger patients. The overall in-hospital mortality rate was 80%. More than three quarters of the decedents died within a week of intubation (P < 0.001). There was no significant relationship between sex and mortality rate (P = 0.535). Conclusion: Our data showed that with increased age there was a decrease in the chance of being extubated. Highlights: There was a significant relationship between outcome of intubated patients with age group and length of being intubated. The most frequent final diagnosis associated with mortality was neuroligic disease (25.2%). Median length of being intubated for survivors was significantly higher than in decedents. Sex was not significantly different between decedents and survivors. Eighty-two percent of the decedents, expired within 7 days of intubation.